Morphological variation of Aphidius ervi Haliday (Hymenoptera: Braconidae) associated with different aphid hosts - Villegas, Cinthya M.; Žikić, Vladimir; Stanković, Saša S.; Ortiz-Martínez, Sebastián A.; Peñalver-Cruz, Ainara; Lavandero, Blas (PeerJ, 2017)
Background Parasitoids are frequently used in biological control due to the fact that they are considered host specific and highly efficient at attacking their hosts. As they spend a significant part of their life cycle within their hosts, feeding habits and life history of their host can promote specialization via host-race formation (sequential radiation). The specialized host races from different hosts can vary morphologically, behaviorally and genetically. However, these variations are sometimes inconspicuous and require more powerful tools in order to detect variation such as geometric morphometrics analysis. Methods We examined Aphidius ervi, an important introduced biological control agent in Chile associated with a great number of aphid species, which are exploiting different plant hosts and habitats. Several combinations (biotypes) of parasitoids with various aphid/host plant combinations were analyzed in order to obtain measures of forewing shape and size. To show the differences among defined biotypes, we chose 13 specific landmarks on each individual parasitoid wing. The analysis of allometric variation calculated in wing shape and size over centroid size (CS), revealed the allometric changes among biotypes collected from different hosts. To show all differences in shape of forewings, we made seven biotype pairs using an outline-based geometric morphometrics comparison. Results The biotype A. pis_pea (Acyrthosiphon pisum on pea) was the extreme wing size in this study compared to the other analyzed biotypes. Aphid hosts have a significant influence in the morphological differentiation of the parasitoid forewing, splitting biotypes in two groups. The first group consisted of biotypes connected with Acyrthosiphon pisum on legumes, while the second group is composed of biotypes connected with aphids attacking cereals, with the exception of the R. pad_wheat (Rhopalosiphum padi on wheat) biotype. There was no significant effect of plant species on parasitoid wing size and shape. Discussion Although previous studies have suggested that the genotype of parasitoids is of greater significance for the morphological variations of size and shape of wings, this study indicates that the aphid host on which A. ervi develops is the main factor to alter the structure of parasitoid forewings. Bigger aphid hosts implied longer and broader forewings of A. ervi.
Keywords: Variability; Biotypes; Geometric morphometrics; Allometry; Wing shape; Wing size; Parasitoids